Fiscal and Monetary Anchors for Price Stability : Evidence from Sub-Saharan Africa. (IMF Working Papers; Working Paper ;, 2008)
The paper presents a model of fiscal dominance with borrowing constraints, and provides evidence for a large number of sub-Saharan African countries on the relative importance of fiscal and monetary determinants of inflation. Based on the dynamic response of inflation to different shocks, including nominal public debt, results show that a number of SSA countries were characterized throughout the period 1980-2005 either by chronic fiscally dominant regimes, with weak or no response of primary surpluses to public debt; or by a consistent adoption of a monetary dominant regime. However, a number of countries were also characterized by lack of a clear monetary and fiscal policy regime. The study also finds that changes in nominal public debt affect price variability via aggregate demand effects, suggesting that fiscal outcomes could be a direct source of inflation variability, as predicted by the fiscal theory of the price level.